PTEN-mTORC2 signaling module controls antibody isotype selection and antiviral humoral immunity - Thapa, Bikash; Lee, Yejin; Pak, Seongwon; Kim, Dongkyu; Kwon, Hyung-Joo; Lee, Keunwook (Frontiers in Immunology, 2026)
IntroductionThe phosphoinositide 3-kinase (PI3K) pathway is a central regulator of activated B cells, yet how PI3K signal strength is interpreted within complex signaling networks to achieve appropriate antibody isotype selection and protective humoral immunity remains incompletely understood. Building on prior work implicating mTOR complexes in germinal center (GC) reactions, we investigated how this circuitry operates under pathological PI3K hyperactivation driven by loss of the PI3K antagonist PTEN.MethodsUsing in vitro GC-like B cell cultures and conditional knockout mouse models, we examined the roles of mTORC1 and mTORC2 downstream of PTEN loss. Transcriptomic profiling, pharmacologic perturbation of Akt and Notch signaling, and in vivo immunization and passive influenza A virus protection assays were employed to define functional and mechanistic outcomes.ResultsPTEN deficiency impaired IgG1 class switching, a defect selectively rescued by genetic inactivation of mTORC2 but not mTORC1. mTORC2 ablation in PTEN-deficient B cells restored Aicda expression and promoted IgG1⁺ plasmablast differentiation without enhancing IgE switching. Transcriptomic analyses revealed that the PTEN–mTORC2 signaling module supports transcriptional programs associated with GC organization, isotype switching, and secretory capacity. Functionally, disruption of mTORC2 in PTEN-deficient B cells reinstated isotype-switched antibody responses, including IgG1, IgG3, and IgA, and restored antibody-mediated protection against influenza A virus infection in a passive immunization setting. Mechanistically, pharmacologic and expression-based perturbations suggested that mTORC2–Akt signaling can cooperate with the Notch pathway to fine-tune IgG1 versus IgE isotype selection.ConclusionTogether, these findings define a PTEN–mTORC2–Akt signaling module within the PI3K network that shapes antibody isotype selection and antiviral humoral immunity, highlighting a potential target for precision modulation of antibody responses in infection, vaccination, and inflammatory diseases.